Exploring the Nexus between Corporate Social Responsibility and Community Engagement: Pathways to Inclusivity and Local Empowerment - Seth, Salil; Pathan, Mohd Irfan (Journal of Emerging Management Studies, 2026)
Purpose – This paper aims to explore the relationship between Corporate Social Responsibility (CSR) and Community Engagement (CE) by examining how CSR initiatives translate into meaningful community development, citizen empowerment, and inclusive social welfare. The study particularly focuses on understanding the underexplored pathway through which CSR strengthens trust, participation, and community legitimacy. Design/methodology/approach – The study adopts a qualitative review-based methodology using conceptual framework analysis. Secondary data were collected from academic journals, government reports, and industry publications through databases such as Scopus, Web of Science, and Google Scholar. The inductive approach based on homogeneity and commonality was used to derive the emergent CSR–CE process. Findings – The findings reveal that CSR acts as a strategic mechanism for mobilizing organizational resources toward community-focused initiatives such as education, healthcare, infrastructure, and environmental development. The output of the study proposes a cyclical CSR–CE model in which CSR strategic intent leads to community engagement outcomes through development initiatives, while continuous feedback from communities refines future CSR priorities. Conclusion – The study concludes that CSR and CE share a mutually reinforcing relationship in which community engagement amplifies the social legitimacy and long-term effectiveness of CSR initiatives. The integration of participatory dialogue and community-centric planning enables firms to achieve both sustainable development and stronger stakeholder trust. Originality/value – The originality of this paper lies in proposing an emergent theoretical CSR–CE model derived through cyclical process, offering a structured explanation of how CSR evolves into sustainable community engagement outcomes. The study extends the conceptual understanding of CSR beyond philanthropy by positioning community engagement as a strategic and cyclical process.